Analytical Solution of Dirac Equation for Hyperbolic Manning-Rosen-like Potential Using Hypergeometric Method for Exact Spin Symmetry. (January 2019) - Pamungkas, Oky Rio; Ma'arif, Miftahul; Suparmi,; Cari,
Abstract: Analytical solution of Dirac equation for hyperbolic Manning-Rosen-like potential is obtained using hypergeometric method. The analytical solution is aimed to determine energy spectrum and radial wave function for this potential with exact spin symmetry. Behavior of atomic particles can be clearly understood if the energy spectrum and wave function of particle are known. Dirac equation for exact spin symmetry is reduced into a second order differential equation like Schrödinger equation. Hypergeometric method for Dirac equation with hyperbolic Manning-Rosen-like potential is the same as for Dirac equation with general hyperbolic Manning-Rosen potential. Energy spectrum is exactly obtained in the closed form and the radial wave functions are expressed in the form of hypergeometric method.